Border marker - Sweden/Finland Border - photograph ... - Campbell, Sandy (University of Alberta Library, 2011)
The border between Sweden and Finland is in the middle of a river channel that runs between the towns of Tornio, Finland (right) and Haparanda, Sweden (left). The border is marked by red poles in the water. While crossing from one town to the other means that you must switch language, currency, time zone and driving laws, people move freely between the two towns. ...